Implikasi Pemekaran Wilayah Daerah Otonomi Baru di Papua - Gusprinadi, Hanes; Tamrin, Tamrin; Irawati, Irawati (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2024)
Â AbstractÂ Autonomous region is a term used to refer to a region that has the authority to regulate its own regional affairs. Based on Article 1 number 12 of Law 23/2014, an Autonomous Region is defined as a legal community unit that has certain regional boundaries and can be in the form of a province, city and district. Decentralization is a form of handing over government authority by the central government to autonomous regions so that they can regulate and manage their government. In 2022, Papua will experience regional expansion, resulting in four new provinces.Â Keywords: New Autonomous Region, Decentralization, PapuaAbstrak Daerah otonom adalah istilah yang digunakan dalam menyebut suatu daerah yang memiliki wewenang dalam mengatur urusan daerahnya sendiri. Berdasarkan Pasal 1 angka 12 UU 23/2014, Daerah Otonom didefinisikan sebagai kesatuan masyarakat hukum yang mempunyai batas daerah tertentu dan dapat berupa provinsi, kota, dan kabupaten. Desentralisasi adalah suatu bentuk penyerahan wewenang pemerintahan oleh pemerintah pusat kepada daerah otonom agar bisa mengatur dan mengurus pemerintahannya. Pada tahun 2022, Papua mengalami pemekaran daerah, dimana menghasilkan empat provinsi baru.Kata kunci : Daerah Otonomi Baru, Desentralisasi, Papua